2016
DOI: 10.12938/bmfh.2015-013
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of fermented milk supplemented with synbiotics can influence the physiological condition of Wistar rats in a dose-sensitive and sex-specific manner

Abstract: Fermented milk supplemented with two probiotic strains (Bifidobacterium lactis Bi-07 and Lactobacillus acidophilus NCFM) and a prebiotic (isomaltooligosaccharide) was orally administered to Wistar rats for 30 days using three dosages. A commercial yogurt was used as a placebo. After treatment, the total protein, hemoglobin, and albumin levels in serum were significantly increased in female rats compared with those in the control group (p<0.05), whereas no significant change occurred in the male rats. A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…The effect of goat milk kefir on parameter of RBC in this study different with a previous study that fermented milk supplemented with probiotics (Bifidobacterium lactis Bi-07 and Lactobacillus acidophilus NCFM and a prebiotic (isomaltooligosaccharide) showed significantly different on HGB in rats compared with the control group [31]. However, the result of the present study was similar with a study by Rosa [19] that kefir had no effect on HCT in normal rats.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of goat milk kefir on parameter of RBC in this study different with a previous study that fermented milk supplemented with probiotics (Bifidobacterium lactis Bi-07 and Lactobacillus acidophilus NCFM and a prebiotic (isomaltooligosaccharide) showed significantly different on HGB in rats compared with the control group [31]. However, the result of the present study was similar with a study by Rosa [19] that kefir had no effect on HCT in normal rats.…”
Section: Discussionsupporting
confidence: 85%
“…The present finding for serum triglyceride is in agreement with findings of AL-Kehayaz (2015) and Halaby et al (2015) who reported decrease in serum triglyceride level on feeding yoghurt and fermented milk (Miao et al, 2016) to rats. Kawase et al(2000) reported a decrease of triglyceride levels in humans when fed with combined supplementation of Lactobacillus casei and Streptococcusthermophilus.…”
Section: Cholesterol and Triglyceridesupporting
confidence: 93%
“…reuteri inhibited TNF-α mRNA in jejunum and ileum of male mice, but not in female mice [ 37 ]. In another study, fermented milk supplemented with synbiotics altered the nutritional index of the rats and these changes were more prominent in female rats [ 38 ].…”
Section: Discussionmentioning
confidence: 99%